HYDRO-DE-AROMATIZATION OF PARAFFIN WAX (Journal of Engineering, 2005)
Iraqi paraffin wax (1.0 wt% aromatic content and 4.4 wt% oil content, Basrah origin) was hydro treated over commercial Pt-Re/y-Al203 catalyst in order to study aromatic removal reaction (de-aromatization) kinetics. Reaction temperature varied from 453 to 533 K over a liquid hourly space velocity from 0.5 to 4.2 h. Hydrogen pressure was kept constant throughout all the experiment at 3.6 Mpa with hydrogen to wax ratio about 400 m/m Kinetics analysis showed that the hydro-de-aromatization reaction followed a second order kinetics model. Energy, enthalpy and entropy of activation of hydro-de-aromatization reaction were 17.2 RJ/mole, 13.1 kJ/mole and -16.9 J/mole K, respectively.